The New Urban Fiscal Crisis - Kirkpatrick, L. Owen (Politics & Society, 2016)
Numerous U.S. cities suffered immense fiscal strain following the subprime mortgage crisis and financial crash of 2007–8. Diminished revenues, tightened credit, and speculative financing that went bad in the aftermath fueled widespread fiscal distress on the local scale. Although the current moment resembles fiscal crises that crested in cities in the 1970s–90s, two factors distinguish the current period. First, municipal affairs have become thoroughly financialized—dominated by speculative securities and volatile debt arrangements—such that local crisis can no longer be understood apart from financial market instability. Second, local fiscal politics have become increasingly removed from democratic oversight and control. This de-democratization hinders the capacity of political communities to reregulate markets and rebuild urban communities. An analytic model derived from the work of Hyman Minsky and Karl Polanyi emphasizes how cities become ensnared in a “financial instability” cycle and how communities seek to protect themselves by way of the “double movement.”
Keywords: Chicago; Detroit; MINSKY, Hyman; United States - economic conditions; de-democratization; financialization; municipal bonds; municipal finance; recessions - 2008-2013; urban fiscal crisis